Evaluation of the 1996 UPV-CM BS in Accountancy graduating students' literacy level in DOS, Word processing and Spreadsheet - Alli, Aileen; Banagodos, Sharon; Cabradilla, Nolan; Garin, Christine; Octaviano, Joan. (1996.)
The ability to operate and troubleshoot a computer is necessary any employee of a company. Three of the basic and important areas are Disk Operating System (DOS), Word Processing (Wordstar), and Spreadsheet (Lotus 1-2-3). One of the computer courses under the BS in Accountancy program of the UPV-CM is BA 183.1 (Computer Application and Methods I) which covers these three areas. This study aims to answer the general question: What is the 1996 UPV-CM BS in Accountancy graduating students' literacy level on DOS, Word processing and Spreadsheet. Specifically, this paper would endeavor to answer the following questions: 1) how knowledgeable are the 1996 UPV-CM BS in Accountancy graduating students' literacy level on DOS, Word processing and Spreadsheet? 2) What are the factors that affect the students' literacy level in DOS, Word Processing and Spreadsheet? The dependent variable identified is the literacy level of the 1996 UPV-CM BS in Accountancy graduating students' literary level on DOS, Word processing and Spreadsheet. The dependent variables pertain to the demographic characteristics, psychomotor, psychological factors and learning environment. The data analyzed was collected through individual distribution of questionnaires to the target population of 58 students wherein 54 where returned. The survey data was collected by means of a questionnaire to elicit the number of basic commands and operation on DOS, Word processing and Spreadsheet knowledgeability and awareness related information as well as identification of factors that affect the amount of knowledge on the commands and operations of the said programs. From the three basic software identified, word processinng had a 72.78% result. The students indicated 67.48% level of knowledge on the commands and operations on Spreadsheet and 67.15% on Disk Operating System. As such, the respondents indicated satisfactory (60-79%) literacy level on DOS, Word processing and Spreadsheet.. The following factors play important influence on the learning abilities of the respondents : Physical factors (computer related physical ailments); Demographic characteristics (gender, financial, and computer education outside UP); Psychological (attitude, habit interest, influences of family, peers, teachers, and technology); Learning Environment (Teacher, teaching techniques and startegies, computer facilities and computer room, computer related services.). The researchers recommend that the respondents be trained in areas where thy are weak. It is also recommended that the respondents behaviour and responses on the factors considered which affects their literacy level on DOS, Word Processing and Spreadsheet should be taken in consideration by the College of Management Faculty in charge of computer related education to increase literacy level from satisfactory to excellent level.
Research Paper (BA 200-Business Research). -- Iloilo City : University of the Philippines in the Visayas, College of Management, March 28, 1996